Interleukin‐37 promotes DMBA/TPA skin cancer through SIGIRR‐mediated inhibition of glycolysis in CD103+DC cells - Fan‐lian Zeng; Xiao‐yan Wang; Ya‐wen Hu; Zhen Wang; Ya Li; Jing Hu; Jia‐dong Yu; Pei Zhou; Xiu Teng; Hong Zhou; Hua‐ping Zheng; Fu‐lei Zhao; et al. (MedComm)
Abstract Interleukin 37 (IL‐37), a member of the IL‐1 family, is considered a suppressor of innate and adaptive immunity and, hence is a regulator of tumor immunity. However, the specific molecular mechanism and role of IL‐37 in skin cancer remain unclear. Here, we report that IL‐37b‐transgenic mice (IL‐37tg) treated with the carcinogenic 7,12‐dimethylbenzoanthracene (DMBA)/12‐o‐tetradecylphorbol‐13‐acetate (TPA) exhibited enhanced skin cancer and increased tumor burden in the skin by inhibiting the function of CD103+ dendritic cells (DCs). Notably, IL‐37 induced rapid phosphorylation of adenosine 5‘‐monophosphate (AMP)‐activated protein kinase (AMPK), and via single immunoglobulin IL‐1‐related receptor (SIGIRR), inhibited the long‐term Akt activation. Specifically, by affecting the SIGIRR‐AMPK‐Akt signaling axis, which is related to the regulation of glycolysis in CD103+DCs, IL‐37 inhibited their anti‐tumor function. Our results show that a marked correlation between the CD103+DC signature (IRF8, FMS‐like tyrosine kinase 3 ligand, CLEC9A, CLNK, XCR1, BATF3, and ZBTB46) and chemokines C‐X‐C motif chemokine ligand 9, CXCL10, and CD8A in a mouse model with DMBA/TPA‐induced skin cancer. In a word, our results highlight that IL‐37 as an inhibitor of tumor immune surveillance through modulating CD103+DCs and establishing an important link between metabolism and immunity as a therapeutic target for skin cancer.